Restore Enthusiasm And Motivation For Student Learning After The Pandemic To Prepare For Future Goals - Mislan; Puji Setyaningsih; Galih Farhanto; Moh. Agung Setiabudi; Donny Setiawan; Wawan Setiawan (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
The Covid-19 pandemic has been around for more than two years. One of them is Indonesia. School closures are one of the consequences of Covid-19 for the world of education. In the face of the Covid-19 pandemic, educational institutions such as schools carry out online or online learning processes (in the network) as an effort to stop the spread of the Covid-19 virus. After approximately 2 years of face-to-face learning held again, of course it will cause changes in the learning process and there will be adjustments to the new habits of students after online learning. In addition, one of the impacts that affect learning is the enthusiasm and motivation of school students to learn. During the pandemic, of course, online learning that is less effective and maximally makes a significant impact on the way students learn, who tend to only be given assignments, of course, causing boredom, which can certainly have an impact on other aspects. The return of students' enthusiasm and motivation to learn does not just happen in a short period of time, but takes a long time because of a new adaptation process with new learning activities. All elements involved in the student learning process, both in the school and home environment, must all be interrelated and support one another.